Ефективність переробки та реалізації молока в аграрних підприємствах : автореферат дисертації на здобуття наукового ступеня кандидата економічних наук - Демчук, Олена Миколаївна; Demchuk, Olena (Дніпро : ДДАЕУ, 2016)
UA: Дисертація на здобуття наукового ступеня кандидата економічних наук за спеціальністю 08.00.04 – економіка та управління підприємствами (за видами економічної діяльності). – Дніпропетровський державний аграрно-економічний університет, 2016. Дисертація присвячена дослідженню теоретичних, методичних та практичних аспектів формування ефективності переробки та реалізації молока в аграрних підприємствах. У роботі розглянуто тлумачення понять «ефективність виробництва», «аграрне підприємство», обґрунтовано методичні підходи щодо дослідження економічної ефективності діяльності аграрних підприємств. У роботі проаналізовано ефективність переробки та реалізації молока в аграрних підприємствах згідно показників, наведених у методиці дослідження. Виявлено вплив факторів маркетингового середовища на діяльність аграрних підприємств. У роботі обґрунтовано модель поведінки споживача на ринку молока. Автором обґрунтовані стратегії розвитку аграрних підприємств, що дасть змогу зайняти конкурентну позицію на ринку. Обґрунтовані напрями підвищення ефективності переробки та реалізації молока, що базуються на принципах теорії гри та моделі ієрархії. /// EN: The thesis for the scientific degree of candidate of economic sciences, specialty 08.00.04 – Economics and Management of Enterprises (by economic activity). Dnipropetrovsk State Agrarian and Economic University, 2016. The thesis have the theoretical generalization done and suggestion on solving the scientific problem made – improving the processing efficiency and marketing milk by implementing the strategy of agricultural enterprises development, which are the basis for the following conclusions: Profound interpretation of the processing efficiency and marketing milk, considered as the impact of business entities in the value added goods formation, which involves promoting the final product on an industrial basis. Groups of factors, that affect the performance efficiency of agricultural enterprises in the marketing environment at the macro and macro level, have been systematized. At the macro level, under the terms of production, processing and marketing of milk the factors were grouped by legal, demographic, socio-cultural, natural and environmental, scientific and technological grounds. At the micro level factors are distributed by market players, such as competitors, suppliers, customers, contact audience. The methodical approach analyzing the efficiency of processing and marketing milk by operating activities (production, processing and marketing) at agricultural and processing enterprises has been substantiated. The thesis states the profitability and sales to be the main performance indicators of processing and marketing. For in-depth study of the efficacy of milk marketing the thesis approved the cost of sales indicator of one unit of sales, which is calculated as the ratio of the difference between total and production cost of sales to sales, which deepens the study of the products implementation efficiency. Summarizing the analysis results of agricultural enterprises development made it possible to establish that despite the gradual decrease in the number of cows on farms in 2010-2014, there is the increased revenue from the sale of milk both in agricultural and processing enterprises. However, this is not the stable production efficiency, such as profitability, sales and earnings per unit calculation. According to correlative-regressive and cluster analysis conducted were identified the regions with retail turnover size per 1000 inhabitants calculations, typical for the Dnipropetrovsk, Cherkasy and Zaporizhzhya regions. The results of quantitative factors impact on marketing environment by expert studies showed that the major influence provide the macro factors. The thesis stresses that this situation demonstrates the inability to respond to changes in the environment of a single agricultural enterprise. It is proved that the negative impact is mostly done by group of economic factors. However, the paper introduces the negative impact of "suppliers" factors due to insufficient load capacity of processing enterprises, reduce, and in some regions of the gradual destruction, the number of cows on farms, low quality of raw materials and lack of established logistics. The paper has established that the efficiency of milk marketing of processing enterprises practically depends on cost of goods sold and the full range of products. The influence of reducing the number of cows on the price of the purchase and sale of commodity milk at the regional level is revealed. In the paper the depth study proves the two farms specializing in milk production to have failed logistics cycle: production processing and manufacturing-selling. The paper notes that potential of logistics processes combination at the farm allows ensuring efficient milk production, even in the natural and economic conditions that are not conducive to the development of the dairy industry. The model of consumer behavior on the milk market in Ukraine by socio graphic, demographic and geographic characteristics has been approved. Most consumers prefer domestic producers and support the decision to dairy enterprises expanding their range, which indicates a sufficient number of potential buyers of dairy products. During the investigation it was discovered that on the choice of place to buy from influence prices, the breadth of the range and quality of products. It has been acknowledged the great demand for dairy products in plastic bottles and carton long-term storage. In order to form the ways of improving the efficiency of processing and marketing of milk the strategy of agricultural enterprises development has been approved. It was established that for most products processing enterprises growth in sales leads product strategy by winning new market segments. Processing enterprises, which occupy a low market share while sales growth are proposed to use a strategy of selective development through increased spending on promotion of the final product, improving product competitiveness, deepening the products range. That determines their future strategy towards the implementation of new technological developments to reduce costs and provide competitive advantages compared to products with processing enterprises production. The paper suggests the ways to increase the efficiency of processing and marketing of agricultural and processing enterprises, the choice is based on decision-making in an uncertain space by the theory of the game. The results of the use of selected efficiency areas are based on the principles of private enterprise “Molokozavod-Olkom” and public company “Plemzavod “Stepnoy”. The calculations in the paper confirmed that the maximum profit per unit sold in the surveyed enterprises will be obtained by implementing the new technologies of milk processing, as well as the introduction of high quality packaging of milk. At the same time, the agricultural enterprises when making decisions to improve the efficiency in modern conditions are offered to use marketing activities, such as innovative packaging of milk.
The efficiency of processing and distribution of milk in the agricultural enterprises
Keywords: ефективність; переробка; реалізація; молоко; стратегія розвитку; аграрні підприємства; efficiency; processing; sale; milk; development strategy; agricultural enterprises